(2x^2-3x+1)(2x^2+5x+1)=9x^2посмотрим что (могу и ошибиться,ибо все делаю не так как надо)1.)приравниваем к нулю: (2x^2-3x+1)(2x^2+5x+1)-9x^2=0 2.) раскрываем скобки: 4x^4 +10x^3+2x^2 -6x^3-15x^2-3x+2x^2+5x+1-9x^2=0 4x^4+4x^3-20x^2+2x=-1 3)выносим за скобки 2x: 2x(2x^3+2x^2-10x+1)=-1 2x=-1, x1=-0,5дальше,продолжаем2x^3+2x^2-10x+1=-1,отсюда 2x^3+2x^2-10x=-2,отсюда 2x за скобки снова: 2x(x^2+x-5)=-2, 2x=-2, x2=-1 x^2+x-5=-1,отсюда x^2+x=4, отсюда x за скобки: x(x+1)=4, x3=4, x4=3x1+x2+x3+x4=-0,5+(-1)+4+3=-1,5+7=5,5
(2x^2-3x+1)(2x^2+5x+1)=9x^2посмотрим что (могу и ошибиться,ибо все делаю не так как надо)1.)приравниваем к нулю: (2x^2-3x+1)(2x^2+5x+1)-9x^2=0 2.) раскрываем скобки: 4x^4 +10x^3+2x^2 -6x^3-15x^2-3x+2x^2+5x+1-9x^2=0 4x^4+4x^3-20x^2+2x=-1 3)выносим за скобки 2x: 2x(2x^3+2x^2-10x+1)=-1 2x=-1, x1=-0,5дальше,продолжаем2x^3+2x^2-10x+1=-1,отсюда 2x^3+2x^2-10x=-2,отсюда 2x за скобки снова: 2x(x^2+x-5)=-2, 2x=-2, x2=-1 x^2+x-5=-1,отсюда x^2+x=4, отсюда x за скобки: x(x+1)=4, x3=4, x4=3x1+x2+x3+x4=-0,5+(-1)+4+3=-1,5+7=5,5
Объяснение:
a)
(3x-1)/x² + (x-9)/3x= [3(3x-1)+(x-9)]/ 3x²= (9x-3+x²-9x)/3x²=
= x²-3 /3x²
b)
1/(2a-b) - 1/(2a+b) = (2a+b-(2a-b))/ (4a²-b²) = (2a+b-2a+b)/(4a²-b²)=
= 0/(4a²-b² = 0
c)
5/c+3) - (5c-2)/(c²+3c) = (5c-5c+2)/(c²+3c) = 2/(c²+3c)